Inclusion in extracurricular activities within primary schools in Botswana: Experiences of children with intellectual disabilities - Tshegetsang, Bokamoso Isago B (Department of Health and Rehabilitation Sciences, 2023)
Introduction: The purpose of this study was to understand children with intellectual disabilities' (ID) experiences of inclusion in extracurricular activities (ECAs) within inclusive primary schools. Problem: Internationally, researchers have noticed that, even within supposedly inclusive spaces like inclusive schools, children with disabilities are still lagging behind in participating and benefitting from extracurricular activities (ECAs) at a comparative rate as their non-disabled peers. Rationale: Children with ID were purposively targeted because literature indicates that they are more likely to be excluded from participating in ECAs or leisure activities with peers than any other group of disabled children. The study will help in the development of inclusive ECAs to better meet the needs of students with intellectual disabilities - particularly in African settings like Botswana where the adoption of inclusive education is still in its infancy. Aim: To describe how children with intellectual disabilities experience inclusion in extracurricular activities within their school as well as to determine the facilitators and barriers to children with intellectual disabilities' inclusion in ECAs within their school. Method: Three data collection methods were used to collect data. Draw and tell interviews and focus group discussions with video vignettes as conversation prompters were used to solicit information from children with ID whilst semi-structured interviews based on the information solicited from conversations with children with ID were used to interview teachers at the school. Findings: The main themes were “access”, “participation”, “effects of ECAs” and “belonging”. Discussion: Factors such as knowing other participants in the ECA, enjoyment of the actual ECA by children with ID, information about the available ECAs offered in the school as well as familial support in the form of valuing and encouraging participation in ECAs were some of the factors and processes that influenced whether and how children with ID engage in extracurricular activities in the school. Conclusion: Although children with ID participate in ECAs differently compared to peers without disabilities, this participation is no less valued by these children and it is important that we continue asking them what we can do or keep on doing to improve ECA service delivery.